Almost but not quite eating pork: Culinary nationalism and Islamic difference in millennial French comedies. (1st December 2015) - Wallenbrock, Nicole Beth
As the anti-immigration sentiment swells in France, cuisine becomes increasingly laden with nationalist discourse. In a post-9-11 European market, the halal label is lucrative, but also inflammatory. In this setting, pork, religiously forbidden to Jews and Muslims, is embedded in xenophobic concepts of nation, as well as in mainstream views of Franco-French identity. The pork restriction remains a primary tool for marking the Muslim Other. The Franco-Maghrebian comedy, a production starring actors of North African origin, thrives largely on this tension, promoting and teasing nationalism with pork humour. This article uses The Society of the Spectacle (1967) by Guy Debord to describe the relationship of pork humour to political practice in millennial France; contemporaneous events (such as the Bloc Identitaire anti-halal protests) also reflect and encourage a similar simplistic reading of Islam. After establishing pork humour in the Franco-Maghrebi features, it closely studies what Homi Bhabha would label a hybrid, Mohammed Dubois (Ona, 2013). Ona's film contributes and yet subverts the pork-humour formula with a Franco-French protagonist who seeks to appear North African when eating a lamb eye, reversing the common pork-humour formula.